2021
DOI: 10.3390/ijerph18020413
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy and A-PRF Pre-Treated Implants in Severe Periodontitis: A Case Report

Abstract: Implantation is currently the best option for tooth replacement in periodontitis. Some major contraindications for the immediate implant are acute periodontitis and active infection. We present the case of a 51-year-old female patient with the highest grade and stage periodontitis treated with advanced platelet-rich fibrin-enriched zirconia implants and with hyperbaric oxygen therapy (HBOT). In particular, HBOT before and after implantation promoted bone regeneration and implant integration, also providing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…113 Giacon et al study with anaerobic Bacteroides Meaninogenicus, in which the effect of HBO therapy on aggressive periodontitis was investigated, it was observed that the number of bacteria decreased significantly in those treated with HBO therapy compared to the control group (increased from 96.5% to 34.5%). 114 Gajendrareddy et al observed that type 1 collagen expression measured at 15 and 28 days was higher and collagen accumulation, maturation and thickness were better in rats treated with 2 hours of HBO treatment per day. 115 HBO treatment is known to have a favourable effect on wound healing because it breaks the hypoxia cycle at every stage.…”
Section: Biomolecule Delivery and Additive Manufacturing For Periodon...mentioning
confidence: 98%
“…113 Giacon et al study with anaerobic Bacteroides Meaninogenicus, in which the effect of HBO therapy on aggressive periodontitis was investigated, it was observed that the number of bacteria decreased significantly in those treated with HBO therapy compared to the control group (increased from 96.5% to 34.5%). 114 Gajendrareddy et al observed that type 1 collagen expression measured at 15 and 28 days was higher and collagen accumulation, maturation and thickness were better in rats treated with 2 hours of HBO treatment per day. 115 HBO treatment is known to have a favourable effect on wound healing because it breaks the hypoxia cycle at every stage.…”
Section: Biomolecule Delivery and Additive Manufacturing For Periodon...mentioning
confidence: 98%
“…Nilai ini menunjukkan kemampuan paruparu dalam menyediakan oksigen bagi darah. Penurunan nilai PO2 dapat terjadi pada penyakit paru obstruksi kronik, PPOK, penyakit obstruksi paru, anemia, hipoventilasi akibat gangguan fisik atau neoromuskular dan gangguan fungsi jantung [15]. Nilai PaO2 kurang dari 40 mmHg perlu mendapatkan perhatian.…”
Section: Hasilunclassified
“…A study by Mulawarmanti et al (2019) in animals with diabetes and periodontitis showed a statistically significant reduction in IL-1β expression and an increase in IL-10 expression after treatment with HBO and HBO in combination with 3% Stichopus hermanii gel [27]. Giacon et al (2021) presented a case report on the use of HBO in combination with advanced plateletrich fibrin (A-PRF) as preparation for immediate implantation in a patient with advanced peri-implantitis [28].…”
Section: Hyperbaric Oxygen Therapy-study Rewievmentioning
confidence: 99%